Value Chain Analysis of Native Chicken in Selected Barangay of Partido - Relucio, Janet (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
The study aimed to analyze the existing value chain of native chicken in the Partido Camarines Sur. Specifically it aimed to describe the value chain in terms of actors, their roles, and links in the value chain map; relationship dynamics among actors; determine the cost and return of native chicken production and identify constraints and opportunities. The study utilized quantitative and qualitative research design. Surveyquestionnaire was used to gather the relevant data needed in the study. Value chain mapping was used to analyze the actors, their roles and relationship dynamics as well as the cost and return analysis to determine the cost and value added in the value chain. Findings revealed the main actors along this value chain are native chicken farmers/raisers, wholesalers/middlemen and retailers. The native chicken farmers directly sold their harvest to the wholesalers/middlemen and eventually to the consumers who directly visited their place. On the other hand, the wholesaler/middlemen sold the native chicken directly to the market. Findings revealed that all the three actors profited in the industry however, the wholesalers/middlemen profited a lot as compared to the producer/raisers and retailers. Results shows that in negotiating the price, the seller is the one sets the price in the value chain from raiser to the wholesalers/middlemen but when it comes to wholesalers/middlemen to consumers the buyers set the price.